The form and meaning of language motifs in phishing crimes: A forensic linguistic study - Ariyanto, Zahy Riswahyudha; Rahmawati, Laili Etika (Universitas Dian Nuswantoro, 2025)
The urgency of this research is that phishing crimes are rife, which are wrapped in persuasive and manipulative language. This research aims to describe the form and meaning of language used in phishing actions based on a forensic linguistics perspective. This type of research is qualitative research with descriptive methods. The descriptive data in this research is in the form of text transcriptions of messages and information indicated in phishing crimes. Research stages include: (1) data documentation; (2) data classification; (3) data analysis; (4) interpretation of form and meaning based on a forensic linguistic perspective; and (4) data conclusion. The data in this research are messages or information in phishing actions. The data sources in this research come from social media and digital forums and social media which are often a means of cyber crime such as WhatsApp, Facebook, Twitter. Data collection techniques use documentation techniques. The data validity test was carried out using theoretical triangulation. The data analysis technique uses discourse analysis, researchers identify language patterns used in phishing crime communications. The results of this research show that the forms of language motives in phishing crimes include (1) 10 deceptive phishing; 4 Phishing APKs; (6) smishing. and the meaning of language motifs in phishing crimes. The conclusion of this research is that there are various types of phishing crimes packaged in persuasive and manipulative language. In this research, forms of phishing action have been found including deceptive phishing; APK phishing; smishing, and the meaning of language motifs in phishing actions has been identified.